THE NORTH CAUCASIAN PRESS ABOUT TERRORISM - PETUKHOV, Valery (CENTRAL ASIA AND THE CAUCASUS, 2005)
All extremist organizations rely on aggressive and deliberate scare tactics to achieve their aims. They seek not so much to procure propaganda effects or unlikely concessions from the authorities as to have a social and psychological impact on society as a whole. They concentrate on discrediting the power-wielding structures to undermine public confidence in them, achieve greater sociopolitical disintegration, and widen the gaps within society. Their main aims, however, are to teach people to fear them, plant feelings of depression in their minds, and deprive people of confidence in their own future. The attempts to use the media to achieve these aims naturally run counter to the state and the law enforcement structures’ efforts to use the media to prevent terrorist acts and their tragic results. The dichotomous trends intertwine to form one single information core and actualize the role of the press and the Internet publications, making them markers of information-psychological warfare in people’s minds. The Northern Caucasus, which has become a zone of terrorist risks, found itself in the center of the information warfare waged by the terrorists and the federal and local power bodies. The press of the North Caucasian republics, territories, and regions can potentially influence the local population in view of the high prestige the press traditionally enjoys there.